PGM1 deficiency diagnosed during an endocrine work-up of low IGF-1 mediated growth failure. Issue 6 (1st November 2016) - Zeevaert, Renate; Scalais, Emmanuel; Muino Mosquera, Laura; De Meirleir, Linda; De Beaufort, Carine; Witsch, Michael; Jaeken, Jaak; De Schepper, Jean
Abstract : Objective and importance : Phosphoglucomutase 1 (PGM1) deficiency, first described as a glycogenosis (type XIV) is also a congenital disorder of glycosylation (CDG). We want to illustrate the wide clinical spectrum of PGM1 deficiency and in particular the associated disturbance in glucose metabolism and the endocrine dysfunction. Treatment withd -galactose is experimental.Case presentation : PGM1 deficiency was diagnosed in an 8-year-old boy, who was referred because of an unexplained complex syndrome, including recurrent hypoglycaemia and low IGF-1 mediated growth failure.Conclusion : The timely diagnosis of this disorder is particularly important, becaused -galactose treatment can improve the latter symptoms.